Woman Religious Rights’ Discrimination in King Mongkuts’ Era: an Anthropology Research with Feminist Approach in Novel Anna and the King written by Elizabeth Hand - Festi Himatu Karima (ETERNAL (English Teaching Journal), 2016)
The aim of the research is to reveal women oppression by men which happened in Siam Palace. This condition makes the life aspects in Siam unbalanced, especially those related to religion. Siamese women have different rights in religion, where women got the lower right.This study uses an anthropology and feminism approach, so this study will be more comprehensive. The result showed that there is treatment differentiation between men and women, especially in religious system.